2007
DOI: 10.3844/ajptsp.2007.178.188
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Diabetic Activity of a Fraction from Cissus verticillata and Tyramine, its Main Bioactive Constituent, in Alloxan-Induced Diabetic Rats

Abstract: Abstract:Cissus verticillata (syn. C. sycioides, fam. Vitaceae) is a medicinal plant popularly used in Brazil, for the treatment of diabetes mellitus. The anti-diabetic activity of a fraction from leaves of Cissus verticilllata (MSF, methanol soluble fraction), as well as that of tyramine (TYR) were investigated, in the model of alloxan-induced diabetes, in male Wistar rats. The biochemical parameters studied were: serum glucose, triglycerides (TG), total cholesterol (TC) and very low density lipoprotein (VLDL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 30 publications
2
6
0
Order By: Relevance
“…Moreover, the anti-inflammatory and antioxidant activities of C. rotundifolia have been recently reported (24). Other studies reported the hypoglycemic and hypolipidemic activities of other species of the same genus Cissus, including C. verticillata and C. quadragualis (41,42), supporting the hypoglycemic activity of C. rotundifolia in the present study.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, the anti-inflammatory and antioxidant activities of C. rotundifolia have been recently reported (24). Other studies reported the hypoglycemic and hypolipidemic activities of other species of the same genus Cissus, including C. verticillata and C. quadragualis (41,42), supporting the hypoglycemic activity of C. rotundifolia in the present study.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, the anti-inflammatory and antioxidant activities of C. rotundifolia have been recently reported (24). Other studies reported the hypoglycemic and hypolipidemic activities of other species of the same genus Cissus, including C. verticillata and C. quadragualis (41,42), supporting the hypoglycemic activity of C. rotundifolia in the present study.…”
Section: Discussionsupporting
confidence: 87%
“…The anti-diabetic activity of tyramine extracted from leaves of Cissus verticilllata was reported, in diabetic rats. The plasma glucose, triglycerides and total cholesterol of these rats showed significant reductions, after the treatment with the tyramine( 24 ). It seems that T. pratense as a rich source of isoflavones, flavonoids, pterocarpans, coumarins and tyramine, can be a good medicinal herb for diabetes treatment.…”
Section: Discussionmentioning
confidence: 99%